The Analytical Approach to Evaluate the Bit Error Rate Performance of PLC System in Presence of Cyclostationary Non-White Gaussian Noise - Rahman, M. M.; Alam, M. T.; Ashiquzzaman, M. (IAES Indonesian Section, 2024)
In a Powerline Communication (PLC) system, improper connections of associated hardwires can lead to the generation of unwanted RF signals, overriding the transmitted signal and producing undesired RF spurious signals. Noise in powerlines also arises from the corona effect, voltage impulses, and arcs occurring in transmission and distribution lines, significantly compromising the integrity of the PLC network. Analysis indicates that powerline noise exhibits a non-white cyclostationary characteristic. Due to its severity, PLC noise is categorized primarily as background noise and impulsive noise. This paper evaluates the characteristics of a powerline network under severe noisy conditions, particularly focusing on Cyclostationary Non-White Additive Gaussian Noise (CNWAGN) across broadband and narrow frequency communication channels. Accordingly, an analytical model is developed to specifically examine the bit error rate (BER) in environments affected by non-white additive Gaussian noise. BER and receiver sensitivity are also assessed for various bit rates using MATLAB simulations, demonstrating performance in terms of BER. This analytical model provides a straightforward method to evaluate results across different bit error rates in frequency-dependent and independent scenarios, surpassing traditional approaches. It proves highly effective in assessing Powerline Communication System performance, with analytically derived outcomes closely aligning with simulation results.